Taking the Relationship Between Populism and Healthcare Seriously: A Call for Empirical Analysis Rather Than Moral Condemnation; Comment on "A Scoping Review of Populist Radical Right Parties' Influence on Welfare Policy and its Implications for Population Health in Europe" - Martijn Felder; Iris Wallenburg; Syb Kuijper; Roland Bal (Kerman University of Medical Sciences, 2021)
In this commentary, we reflect on Rinaldi and Bekker's scoping review of the literature on populist radical right (PRR) parties and welfare policies. We argue that their review provides political scientists and healthcare scholars with a firm basis to further explore the relationships between populism and welfare policies in different political systems. In line with the authors, we furthermore (re)emphasize the need for additional empirical inquiries into the relationship between populism and healthcare. But instead of expanding the research agenda suggested - for instance by adding categories or niches in which this relationship can be observed - we would like to challenge some of the premises of the studies conducted and reviewed thus far. We do so by identifying two concerns and by illustrating these concerns with two examples from the Netherlands.